POLEMICAL DEBATES AND THEIR GENRE FEATURES (ResearchJet Journal of Analysis and Inventions, 2022)
The article describes the main typological features of polemical speech and polemical genres. Polemical debates are shown on the basis of examples and given through concrete examples.